Biología comparada de tres especies de salivazo de los pastos del género Zulia (Homoptera: Cercopidae) - Rodríguez Chalarca, Jairo; Peck, DC; Canal, NA (2002)
The biology of three Colombian species of the genus Zulia (Homoptera: Cercopidae) was studied to establish comparative methodologies for the study of the grassland spittlebug complex, obtain new basic information and describe variation at the level of genus. To facilitate the differentiation and recognition of the developmental stages, certain aspects of the external morphology were described and characterized for the four developmental stages of the egg, five instars and adult sexes. To quantify the duration of the developmental stages, eggs were observed under incubation in petri dishes, nymphs in pots on surface roots of Brachiaria ruziziensis Germain and Everard, and adults on pots planted with B. ruziziensis, maintained under acetate cages. Finally, oviposition sites were determined by simulating field conditions in the screenhouse in pots planted with B. ruziziensis. In the eggs of each species there was an increase in size among stages with little variation in external characteristics during development. In the nymphs there was an increase in size between each instar for each of the four parameters evaluated, with the head capsule being the most diagnostic morphological character. The adults presented sexual dimorphism expressed by the greater size of females in the majority of the six parameters evaluated in Z. carbonaria (Lallemand), Z. pubescens (Fabricius) and Zulia sp nov. The duration of the egg stage was 17.4, 14.3 and 14.6 days, respectively; the duration of the nymph stage 42.4, 38.0 and 42.7 days and adult longevity 19.6, 18.4 and 14.2 days, for a total life cycle of 69.6, 61.5 and 64.4 days, respectively. There were significant differences among species in developmental stages and total duration. Z. carbonaria and Zulia sp nov. presented a preference for the soil as oviposition substrate with 99.4 and 100% of recovered eggs, in contrast to Z. pubescens with 59.2% of eggs recovered from the stem surface and 40.4% from the soil. The established methodologies are adequate for describing the biology of Zulia and other spittlebug genera. This new biological information is important for improving the management of these species in forage grasses of Colombia. In addition, the degree of variation in the genus is relevant to the integrated management of spittlebugs and strengthens our understanding of the patterns of variation exhibited by this insect complex.